Resolving the global economic crisis : after wall street. a statement by thirty-three economists from thirteen countries (Special report, 1987)
The world economy is obviously facing substantial difficulties. The huge imbalances in national current account positions -- notably the American deficit and the counterpart surpluses in Japan, Germany, and the Asian NICs -- have generated considerable instability in exchange rates and concernes over the sustainability of the economic expansion.